Replication timing analysis in polyploid cells reveals Rif1 uses multiple mechanisms to promote underreplication in Drosophila. Issue 3 (13th September 2021) - Das, Souradip; Caballero, Madison; Kolesnikova, Tatyana; Zhimulev, Igor; Koren, Amnon; Nordman, Jared
Abstract: Regulation of DNA replication and copy number is necessary to promote genome stability and maintain cell and tissue function. DNA replication is regulated temporally in a process known as replication timing (RT). R ap1-i nteracting f actor 1 (Rif1) is a key regulator of RT and has a critical function in copy number control in polyploid cells. Previously, we demonstrated that Rif1 functions with SUUR to inhibit replication fork progression and promote underreplication (UR) of specific genomic regions. How Rif1-dependent control of RT factors into its ability to promote UR is unknown. By applying a computational approach to measure RT in Drosophila polyploid cells, we show that SUUR and Rif1 have differential roles in controlling UR and RT. Our findings reveal that Rif1 acts to promote late replication, which is necessary for SUUR-dependent underreplication. Our work provides new insight into the process of UR and its links to RT. Abstract : In polyploid cells, copy number is not uniform throughout the genome. Underreplication causes pericentric heterochromatin and defined regions of euchromatin to have reduced copy number relative to overall ploidy. SUUR and Rif1 are key regulators of underreplication, and Rif1 is a known regulator of replication timing (RT). Das et al . take a computational approach to measure replication timing in polyploid cells. Their results demonstrate that, while Rif1 and SUUR both promote underreplication, they differentially affect RT.